Effective Determination of Speed Strength Development Exercises for Male National Team badminton Players Aged 13 - 15 - Kim Ha, Bui (International Journal of Humanities and Education Development (IJHED), 2022)
The results of determining the effectiveness of 45 groups of exercises/exercises to develop strength and speed for male badminton players of the Vietnamese team aged 13-15 after one year of experimentation have brought a difference. The performance of 6 test tests of the experimental group increased significantly over the training period. The percentage of standard ratings of the experimental group was higher and different from that of the previous year's athletes